Unraveling crystalline phases, morphology, hardness, and adhesion of PEO anodic coatings on Ti-15Nb alloy surface - Kuroda, Pedro Akira Bazaglia; Montes, Thiago Henrique; Rossi, Mariana Correa; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (Elsevier, 2024)
This study aims to create a coating of oxide (with Ca, P, and Mg) on the Ti-15Nb alloy using the plasma electrolytic oxidation (PEO) technique. The voltage value was varied during the surface treatment process (200, 250, and 300 V). The PEO treatment was performed using a limited current of 2.5 A for 60 s. The films have the anatase and rutile crystalline structures of TiO2, where rutile increases the hardness of the coatings. All coatings are hydrophilic in contact with distilled water and have poor adhesion to the substrate.
Keywords: Plasma electrolytic oxidation; Surface characterization; Ti-15Nb alloy